Predicting the effect of powertrain preconditioning on vehicle efficiency. Issue 3 (4th May 2017) - Gillot, Romain; Dempsey, Mike; Picarelli, Alessandro
ABSTRACT: Under extreme climatic conditions, the vehicle fuel consumption can be far from the certified value. Given the growing concern for polluting emissions, it is necessary to investigate a way to improve the overall vehicle efficiency and thus reduce the emissions and fuel consumption gap. One solution is to pre-warm the gearbox and the engine in order to make it work at an optimal temperature to achieve the best efficiency possible. Indeed, low lubricant temperature is a source of reduced vehicle efficiency due to the lubricant viscosity rising exponentially at very low temperature. Using the Powertrain Dynamics library, a vehicle model with a detailed equation-based gearbox model taking into account the temperature-dependent losses and a map-based engine including temperature-dependent emission models (CO, NOx, HC and particulates) is developed.